Tropical Vernacular Strategies of Kobuang Limo House for Sustainable Thermal Performance in Society 5.0 Era - Mulfakli; Desy Aryanti (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2026)
This study examines the thermal performance of Kobuang Limo House, a traditional Malay stilt house in Riau, Indonesia, as a model of passive tropical adaptation. Using a quantitative-descriptive method, field measurements of air temperature (Ta), relative humidity (RH), and air velocity (Va) were conducted to calculate the Effective Temperature (ET) based on SNI 03-6572-2001. The analysis focuses on the relationship between architectural configuration, particularly wall openings and attic ceiling conditions to indoor thermal comfort. Results show that houses with ventilated ceilings maintain a stable ET within 26 - 27 °C, while the non-ceilinged unit recorded higher temperatures (~ +0.7 °C). The proportion of wall openings (15–25 %) also contributes to effective cross-ventilation, supporting natural cooling performance. These findings confirm that the passive thermal strategies embedded in Kobuang Limo House remain effective in achieving sustainable indoor comfort and provide empirical evidence for climate-responsive architectural design in the era of Society 5.0.